Desenvolvimento de dinamômetro de chassi para testes de veículos/robôs pequena escala - Lourenço, Maria Augusta de Menezes, 1995- (2020)
Orientadores: Ludmila Corrêa de Alkmin e Silva, Jony Javorski Eckert